Cosmology and social stratification of the Madurese population in the XIX century - Iswahyudi Iswahyudi (Cogent Arts & Humanities, 2022)
The cosmological view of the Madurese up to the 19th century, both macrocosmic and microcosmic, perceived themselves as an integral part of nature, following natural laws even if they were meta-empirical in nature. This is a belief that is believed to originate and refer to the pre-Islamic Madurese belief model. In the view of the adherents of determinism, the actions and beliefs of humans and society are influenced by a variety of factors such as geographic, biological, psychological, sociological, economic, religious, environmental, customs, traditions and social norms, because of these different factors the moral of society is not same. The religiousness and social stratification of the Madurese community does not provide much of a cosmological-philosophical dimension regarding environmental preservation. Broadly speaking, the social stratification or stratification of the Madurese community consists of three layers, namely oreng kene or what is called oreng dume as the lowest level of society, ponggaba as the middle layer, and parijaji or priyayi as the top layer of society. Religion does not provide much of a cosmological-philosophical dimension in the religiosity of Madurese society. Based on this analytical descriptive research, it can be seen that their cosmological tradition up to the nineteenth century was very strongly influenced by Javanese cosmology which put forward the principle of harmony and harmony with nature and supernatural beings.